2012
DOI: 10.1111/j.2041-1294.2012.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation‐Induced Changes in Trombay Nuclear Waste Glass Containing Iron

Abstract: Alkali-based barium borosilicate glasses having similar composition to the Trombay nuclear research reactor waste base glass containing iron were prepared and irradiated by gamma rays. The radiation-induced defect centers were investigated using electron paramagnetic resonance (EPR) technique. The results showed the formation of silicon hole centers and electron trap centers apart from boron-based oxy hole centers in the glass due to the irradiation. The EPR Hamiltonian parameters for these radicals were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 34 publications
6
47
0
Order By: Relevance
“…Similarly, the breaking of B-O-B bonds at regular sites leads to the formation of BOHC type of radicals in the system. Through the ESR data, the spin density of the radiation induced radicals was evaluated adopting standard procedure [Mohapatra et al (2013)] using a spin counting technique with suitable standard. In the present case, for the highest dose irradiated sample, the spin density was calculated to be 2.8 10 19 spins / 100 mg of the sample which is equivalent to few hundreds of ppm.…”
Section: Investigations By Pl Techniquementioning
confidence: 99%
“…Similarly, the breaking of B-O-B bonds at regular sites leads to the formation of BOHC type of radicals in the system. Through the ESR data, the spin density of the radiation induced radicals was evaluated adopting standard procedure [Mohapatra et al (2013)] using a spin counting technique with suitable standard. In the present case, for the highest dose irradiated sample, the spin density was calculated to be 2.8 10 19 spins / 100 mg of the sample which is equivalent to few hundreds of ppm.…”
Section: Investigations By Pl Techniquementioning
confidence: 99%
“…Long‐term stabilities of the component mechanical properties and dimensionality are required to insure system operation performance under a long exposure of radiations. In the literatures, many studies have been reported covering radiation effects on properties of optical glasses 10−14 and nuclear waste glasses 15−17 . The studies concluded that various types of structural defects were generated in various types of glasses by radiation damages and in turn, adversely impact optical properties or chemical stability of the glasses resulted.…”
Section: Introductionmentioning
confidence: 99%
“…This primary interaction produces electron and hole pairs in the glass [37,45,56]. These mobile charge carriers can be trapped at different sites within the glass structure, forming radiation-induced paramagnetic defects [28,33,56,57]. These paramagnetic defects can be healed by allowing trapped charge carriers to recombine when external energy is supplied [31,57,58].…”
Section: Overviewmentioning
confidence: 99%
“…These mobile charge carriers can be trapped at different sites within the glass structure, forming radiation-induced paramagnetic defects [28,33,56,57]. These paramagnetic defects can be healed by allowing trapped charge carriers to recombine when external energy is supplied [31,57,58]. This energy can be supplied in the form of heat or by coulombic forces [31,57,58].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation